2011
DOI: 10.1159/000333210
|View full text |Cite
|
Sign up to set email alerts
|

Relative Etiological Role of Prior Hepatitis B Virus Infection and Nonalcoholic Fatty Liver Disease in the Development of Non-B Non-C Hepatocellular Carcinoma in a Hepatitis B-Endemic Area

Abstract: Background and Aims: We investigated the relative etiological role of prior hepatitis B virus (HBV) infection and nonalcoholic fatty liver disease (NAFLD) in the development of non-B non-C, non-alcohol or specific cause-related hepatocellular carcinoma (NBNC-NA-NS HCC) in an HBV-endemic area of Korea. Methods: A total of 329 patients with NBNC-NA-NS HCC were enrolled in this study. Prior HBV infection was defined as the presence of isolated IgG hepatitis B core antibody (anti-HBc), and NAFLD was diagnosed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 55 publications
(32 reference statements)
2
53
1
1
Order By: Relevance
“…In our local context, the prevalence of NASH risk factors, such as obesity, increased from 6% in 1998 to 10.8% in 2010, while diabetes mellitus increased from 9% in 1998 to 11.3% in 2010, which intuitively would translate into an increasing prominence of NASH and consequently NASH‐related (i.e., cryptogenic) HCC 10. This can also be extrapolated to many other countries that are afflicted by the burgeoning obesity and diabetes epidemic 31, 32, 33…”
Section: Discussionmentioning
confidence: 93%
“…In our local context, the prevalence of NASH risk factors, such as obesity, increased from 6% in 1998 to 10.8% in 2010, while diabetes mellitus increased from 9% in 1998 to 11.3% in 2010, which intuitively would translate into an increasing prominence of NASH and consequently NASH‐related (i.e., cryptogenic) HCC 10. This can also be extrapolated to many other countries that are afflicted by the burgeoning obesity and diabetes epidemic 31, 32, 33…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, cHCC patients with anti-HBc antibodies were older, showed lower the MELD scores, AFP levels, lower AST/ALT levels, and a smaller proportion of patients with cirrhosis than patients with HBV HCC. [23]. In another study covering 2003-2012, cHCC comprised 6.8% of HCC cases [21].…”
Section: Comparisons According To the Presence Of Anti-hbc Antibodiesmentioning
confidence: 96%
“…In South Korea, the incidence of cryptogenic, or NBNCNA, HCC has reportedly increased from 2.3% to 12.2% [21][22][23][24]. Therefore, there is a need for better understanding of cHCC.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD‐related HCC in the general population is not well documented, with most studies reporting only the proportion of NAFLD‐related HCC in single or multiple institutions and a few studies utilizing a large transplant database or cancer registry to look into the impact of NAFLD‐related HCC in the respective countries where the studies were carried out. A summary of these studies can be found in Table . These studies are further discussed in the sections that follow.…”
Section: Resultsmentioning
confidence: 99%